Early Life Stress Induced by Limited Nesting Material Produces Metabolic Resilience in Response to a High-Fat and High-Sugar Diet in Male Rats - Maniam, Jayanthi; Antoniadis, Christopher P.; Wang, Kristy W.; Morris, Margaret J. (Frontiers in Endocrinology, 2015)
Environmental conditions experienced in early life can profoundly influence long-term metabolic health, but the additive impact of poor nutrition is poorly understood. Here, we tested the hypothesis that early life stress (ELS) induced by limited nesting material (LN) combined with high-fat and high-sugar diet (HFHS) post-weaning would worsen diet-related metabolic risk. Sprague-Dawley male rats were exposed to LN, postnatal days 2–9, and at weaning (3 weeks), siblings were given unlimited access to chow or HFHS resulting in (Con-Chow, Con-HFHS, LN-Chow, and LN-HFHS, n = 11–15/group). Glucose and insulin tolerance were tested and rats were killed at 13 weeks. LN rats weighed less at weaning but were not different to control at 13 weeks; HFHS diet led to similar increases in body weight. LN-chow rats had improved glucose and insulin tolerance relative to Con-Chow, whereas LN-HFHS improved insulin sensitivity versus Con-HFHS, associated with increased peroxisome proliferator-activated receptor gamma co-activator-1-alpha (Pgc-1α) mRNA in muscle. No effect of LN on plasma or liver triglycerides was observed, and hepatic gluconeogenic regulatory genes were unaltered. In summary, this study demonstrates that ELS induced by LN conferred some metabolic protection against insulin and/or glucose intolerance in a diet-dependent manner during adulthood.